CRITERION OF CONTROL AND THE RIGHT OF STANDING OF A JURIDICAL PERSON IN ICSID ARBITRATION - Đundić, Petar (Zbornik radova Pravnog fakulteta u Novom Sadu, 2021)
International Centre for Settlement of Investment Disputes (Centre or ICSID) was established for resolving disputes between foreign investors and host States. This is why jurisdiction ratione personae of the Centre depends crucially on who can be considered as a foreign investor, i.e. which persons have right of standing to initiate arbitration based on the Washington Convention on the Settlement of Investment Disputes between States and Nationals of other States (the Convention). When a claimant is a juridical person, one of the issues causing a debate in arbitral practice concerns the significance of control over that entity – to what extant is jurisdiction of an ICSID tribunal affected by the fact that the entity is under direct or indirect control of the host State’s nationals. The paper examines the problem with regards two groups of cases that the Convention regulates separately. The first group concerns cases in which the role of a claimant belongs to juridical persons nominally holding the nationality of other Contracting States of the Convention. The other category relates to the cases of claims submitted by local entities against their own State.